Intradermal injection of a fractional dose of an inactivated HFMD vaccine elicits similar protective immunity to intramuscular inoculation of a full dose of an Al(OH)3-adjuvanted vaccine. Issue 30 (27th June 2017) - Li, Min; Duan, Yueqiang; Yang, Xiaolan; Yang, Qiaozhi; Pang, Baodong; Wang, Yugang; Ren, Tianyu; Wang, Xiliang; Zhao, Zhongpeng; Liu, Songcai
Highlights: Intradermal injection of an inactivated bivalent HFMD vaccine elicits protective immunity. Intradermal and fractional immunization elicits similar protection to conventional inoculation. An inactivated bivalent HFMD vaccine elicits a balanced immunity. Abstract: Enterovirus 71 (EV71) and Coxsackievirus A16 (CVA16) are the two major causative agents of hand, foot and mouth disease (HFMD), which erupts in the Asia-Pacific regions. A bivalent vaccine against both EV71 and CVA16 is highly desirable. In the present study, on the bases that an experimental bivalent vaccine comprising of inactivated EV71 and CVA16 induces a balanced protective immunity against both EV71 and CVA16, we compare the immunogenicity and reactogenicity of one fourth of a full dose of an intradermal vaccine administered by needle-free liquid jet injector with a full dose of an intramuscular vaccine administered by needle-syringe in monkeys. The results suggest that intradermal injection of a fractional dose of an inactivated HFMD vaccine elicits similar immunogenicity and reactogenicity to intramuscular inoculation of a full dose of an Al(OH)3 -adjuvanted vaccine, regardless of whether monovalent or bivalent vaccines were used. Our results support the use of an intradermal bivalent vaccine strategy for HFMD vaccination in order to satisfy the requirements and reduce the costs.